A novel amino acid site closely associated with the neurovirulence of live, attenuated Japanese encephalitis vaccine (SA14-14-2 strain). Issue 11 (4th March 2020) - Yang, Huan; Fan, Fengming; Liu, Lina; Liu, Jie; Sun, Yan; Xie, Anping; Shi, Xiaoling; Liu, Li; Yu, Yongxin; Li, Yuhua; Ge, Yonghong; Zeng, Xianwu; et al.
Highlights: Mutation of 244-site (G → E) enhances the virulence of JEV SA14-14-2 in mice. JEV E244 (G → E) exhibits different virulence in the context of JE vaccine. Minor mutations in vaccine cannot be detected by Sanger sequencing. Minor variants in vaccine do not develop to the dominant population. Abstract: Japanese encephalitis (JE) poses a serious threat to the world's public health yet without a cure, the only way to prevent Japanese encephalitis virus (JEV) infection is vaccination. Live attenuated vaccine (SA14-14-2 strain) is the most widely used JE vaccine, and clinical data have confirmed its safety and effectiveness. Eight sitesassociated with virulence in the Envelope (E) protein are often the focus of quality control of JE vaccine. However, sequences retrieved from NCBI, as well as our previous results showed that the wild strain SA14 may harbor two different amino acids at amino acid residue 244 of the E glycoprotein (E244), and it may be related to virulence. In this study, we introduced a single mutation at nt1708 (G → A) in the full-length cDNA clone of SA14-14-2, replacing a Gly with Glu at amino acid residue 244 of the E glycoprotein, and successfully constructed the mutant virus (JEV E244). JEV E244 exhibited a similar plaque morphology and growth characteristics to JEV SA14-14-2 in cell culture. However, it had lethal neurovirulence in mice and could enter the brain following intraperitoneal inoculation. Moreover, the virulence of JEV E244 in the context of vaccine in mice is significantly different from that of the JEV E244 alone. These results suggested that E244 site should be included in the assessment of the genetic stability of the attenuated JE vaccine. The detection of minor mutations in vaccine population and influence on the safety of vaccine is discussed.